Workshop on Implementing the Independent Curriculum: Differentiated Learning for Junior High School Teachers in West Seram Regency - Fryan Sopacua; Ashari B.P. Dulhasyim; Sally Untajana; Venty Sopacua; Yansen Kapitan; Yulia Lesiela (Pascasarjana Universitas Mataram, 2025)
This community service activity aims to provide a workshop for 15 teachers at SMP Negeri 2 Inamosol to improve their skills in implementing differentiated learning. This workshop is expected to help teachers implement the Independent Curriculum and Differentiated Learning well and acquire new knowledge and skills in dealing with the diversity of students in the classroom more effectively and equitably, so that this can also be reflected in learning tools/modules. In addition, teachers are expected to be able to use interactive learning media that can stimulate student activity so that through this training teachers can not only improve their knowledge and skills related to differentiated learning, but also be able to choose learning methods/models/media that are appropriate to the characteristics of students and materials. The community service team organizes activities based on 4 stages: preparation and provision, implementation, and program sustainability. This community service received a positive response with an average percentage value of teacher responses to the Workshop on Implementing the Independent Curriculum: Differentiated Learning for Teachers of SMP Negeri 2 Inamosol, namely 86.4%, so it can be said that the community service activities at SMP Negeri 2 Inamosol were successful and well received by the principal, teachers, and students